Pemberdayaan Perempuan oleh Lajnah Wanita dan Putri Al-Irsyad Surabaya - Zakiah Zakiah (Balai Penelitian dan Pengembangan Agama Semarang, 2010)
This is a qualitative study on women empowerment conducted by LajnahWanita dan Putri Al-Irsyad Surabaya. The data are gathered using threemethods, namely library research, interviews and observation. Finding of thisresearch shows that the organization being studied has done many empowermentactivities, particularly in this following areas: economic, religious, health and education empowerment. There are many programs which is aimed for empowering women, such as rice distribution, Islamic teaching, health teaching, Islamic education for children and teenagers, and community development.